Customer Satisfaction with the Service of the Lao Development Bank: Xayabuly Branch - DOUANGPHACHAN, Phetdavan; HOONGSENGPHA, Soudthida; SISAVANH, Orlathai (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The objectives of this research were to study customer behavior and Service Affecting Customers' Satisfaction with the Service of the Lao Development Bank's Xayabuly using the 10 service quality theory which includes: Access Communication¸ Competence¸ Courtesy Creditability¸ Reliability¸ Responsiveness¸ Security, Understanding Customers, Understanding and Knowing service. In the analysis of Customers' Satisfaction with the Service of the Lao Development Bank's Xayabuly Branch. The sample group used in this Research is 110 people who actually come to use the services in Lao Development Bank, Xayabuly branch. The tool used in data collection is a questionnaire with 5 levels of Likert Scale with a reliability level of 0.98 (98%) and the SPSS (Version 26) statistical software for data analysis is: percentage, mean, standard deviation. The result of the study on the topic of Service Affecting Customers' Satisfaction with the Service of the Lao Development Bank's Xayabuly Branch. It was found that the service behavior of customers of Lao Development Bank, Xayabuly branch is that most of the customers come to do business to deposit money and choose the type of account as a savings account, by recognizing the service information of Lao Development Bank through online media and the reason why customers choose to use the service because of the quick service, as well as recommending other people to use the services in Lao Development Bank, Xayabuly branch. The satisfaction of customers who come to use services in the Lao Development Bank, Xayabuly branch as a whole is very satisfied. Among them, include: the aspect of goodwill, the aspect of understanding the service recipient, the aspect of quick response, the aspect of access channel, the aspect of ability, the aspect of reliability, the aspect of confidence, the aspect of security, the aspect of understanding the customer-knowing the customer and the aspect of communication respectively, with an average value between 3.41 and 4.20.